2012
DOI: 10.1371/journal.pntd.0001727
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Investigation of Antitrypanosomal Phytochemicals from Nigerian Medicinal Plants

Abstract: BackgroundHuman African trypanosomiasis (HAT), a parasitic protozoal disease, is caused primarily by two subspecies of Trypanosoma brucei. HAT is a re-emerging disease and currently threatens millions of people in sub-Saharan Africa. Many affected people live in remote areas with limited access to health services and, therefore, rely on traditional herbal medicines for treatment.MethodsA molecular docking study has been carried out on phytochemical agents that have been previously isolated and characterized fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 92 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…Some published reports have focused on natural products that are biologically active against one or more protozoan organism or any of their validated drug targets [374][375][376][377][378] while other works have focused on natural products or phytochemicals that were isolated from plants with historical ethnomedicinal therapeutic use [379,380]. Molecular docking has been used to identify, in silico, the selectivity of some compounds or classes of compounds for specific protozoan drug targets.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Some published reports have focused on natural products that are biologically active against one or more protozoan organism or any of their validated drug targets [374][375][376][377][378] while other works have focused on natural products or phytochemicals that were isolated from plants with historical ethnomedicinal therapeutic use [379,380]. Molecular docking has been used to identify, in silico, the selectivity of some compounds or classes of compounds for specific protozoan drug targets.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…coumarin-derived sesquiterpenoid kamalone to be a strongly docking ligand for L. major trypanothione synthase [378]. An in-silico screening study (MolDock) of antiparasitic medicinal plants from West Africa has revealed several phytochemicals with strong, selective docking to a number of Trypanosoma brucei protein targets [379]. This investigation revealed that several triterpenoid and steroid ligands (e.g., grandifoliolenone, lawnermis acid methyl ester, lawsaritol A, wallichianol, 14-hydroxy-isocarpanolide, physagulins J, K, and L, vamonolide, withangulatins E, F, and I, clerosterol, and β-sitosterol, Figure 5) were selective for T. brucei sterol 14α-demethylase.…”
Section: Leishmania and Trypanosoma Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pathway is essential in unicellular parasites from the genus Trypanosoma since they are unable to take up galactose from the environment and rely on "reversing" some of the Leloir pathway reactions in order to generate galactose for glycoprotein synthesis [207][208][209][210][211]. Thus, inhibition of GALE in these species has potential for the development of novel therapeutics [212][213][214][215]. Six inhibitors of F. hepatica UDP-galactose 4-epimerase (EC 5.1.3.2) have been identified; two showed good selectivity over the human enzyme [216].…”
Section: Other Metabolic Pathwaysmentioning
confidence: 99%